(untitled) (Acta Scientiarum. Health Sciences, 2024)
The study aimed to analyze the trajectory and professional practice of graduates of a Residency Program in Obstetric Nursing. It was qualitative, exploratory-descriptive research carried out with twenty-nine members of the residency program in obstetric nursing private in a higher education institution in the central region of Rio Grande do Sul. Data were collected through an online questionnaire from March to July 2021 and interpreted by content analysis. The following categories emerged from the data analysis: Contribution of training to the current scenario of maternal and child health; Difficulties and challenges: the confrontations of training; and from the training received to the expected training. It was revealed that all graduates were female, being few with previous experience when entering the residency program and, after completion, most continued to work in various spaces of maternal and child and obstetric care.